Innovative design of experimental blade cascad model for in-depth analysis of stall flutter - Šnábl, Pavel; Prasad, Chandra Shekhar; Procházka, Pavel; Pešek, Ludek; Uruba, Václav; Skála, Vladislav (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
Stall flutter is a serious threat to the operational integrity in turbomachinery, particularly in the final stage rotors of steam turbines and in compressors. Although computer science has developed rapidly and much of the research can be carried out using numerical tools, the simulation of some phenomena, such as stall flutter, is still very challenging and needs to be supported by experimental data. This paper presents an innovative experimental linear blade cascade design with five prismatic blades with pitch degrees of freedom, designed to be operated in a low subsonic wind tunnel. The geometry of the blade cascade was chosen on the basis of the experimental and numerical tests to allow stall flutter initiation. New suspension, measurement and electromagnetic excitation systems were developed and experimentally tested to allow accurate measurement of aerodynamic damping during controlled flutter tests. The novelty of the experimental blade cascade is the possibility of single pulse excitation of the blades. The cascade can be brought to the edge of stability by adjusting the angle of attack and flow velocity, and then the pulse can be used to induce stall flutter. Measurement of both mechanical and flow characteristics, also demonstrated in this paper, will provide data for in-depth analysis of stall flutter initiation and propagation.